Comparison Between the Original and Shortened Versions of the National Institutes of Health Stroke Scale in Ischemic Stroke Patients of Intermediate Severity. Issue 1 (January 2016) - Lee, Chun Fan; Venketasubramanian, Narayanaswamy; Wong, K.S. Lawrence; Chen, Christopher L.H.
Abstract : Background and Purpose—: The 15-item National Institutes of Health Stroke Scale (NIHSS) has been critiqued for its complexity and variability, and shortened versions have been proposed. This study aimed to compare the measurement properties of the original version with 3 shortened versions with 11, 8, and 5 items, respectively. Methods—: Analyses were performed using data from an international, double-blind randomized controlled trial investigating the efficacy of MLC601 on stroke recovery in patients with ischemic stroke of intermediate severity (Chinese Medicine Neuroaid Efficacy on Stroke recovery [CHIMES]). To compare discriminative ability and responsiveness to change, the effect sizes of the NIHSS scores in relation to modified Rankin Scale, mini-mental status examination, and Barthel index were estimated using regression analysis. Results—: For both discriminative ability and responsiveness to change, the original version exhibited a larger effect size (0.55 and 0.84) in relation to modified Rankin Scale than the other 3 shortened versions (0.35–0.46 and 0.74–0.78). Conclusions—: The original 15-item NIHSS retained information that made it more discriminative and responsive to change than the shortened versions. We recommend future clinical researchers to use the full version NIHSS to evaluate patients' stroke severity. Clinical Trial Registration Information—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00554723. Abstract : Supplemental Digital Content is available in the text.